MODE KEGAGALAN STRUKTUR PIPA PADA CANTILEVER GANDA DUA ARAH - -, Darwinto; Saleh, Agus; Damayanti, Eva; Nuhgraha, Yoddy Agung; Ginting, Edison (Jurnal TEDC; Vol 19 No 3 (2025): JURNAL TEDC, 2025)
The Two-Way Double Cantilever Structure is a structure commonly found in general use. This structure typically consists of a beam that is supported or pinned at one end, while the other end of the cantilever beam operates freely (not supported) and has a specific load at its end. When a load is applied to the open side, the supported end will experience moments that vary in value depending on the load applied. This type of structure is commonly used in applications such as the installation of CCTV in open areas and the installation of lights on public roads. Based on this background, the author aims to conduct research related to the planned material strength, specifically carbon pipe. In addition, the research is conducted to minimise the expenditure that is too large, the aim of which is to design something useful, inexpensive, and with good durability or resilience in its operation. In this study, the method used consists of data collection through literature review, interviews, or direct observation of the positions of the poles that have been installed along the route taken. The results of this research are a robust yet inexpensive double cantilever structure, leading to the conclusion that a good, strong, and load-resistant structure does not necessarily have to be constructed at a high cost.